Influencing Factors of Dyadic Coping Among Infertile Women: A Path Analysis - Tang, Nan; Jia, Yingying; Zhao, Qing; Liu, Huihui; Li, Junzheng; Zhang, Hongchen; Han, Lin; Huangfu, Chaoji (Frontiers in Psychiatry, 2022)
Background: The infertility prevalence of married couples in China is increasing gradually. The dyadic coping level and its influencing factors of infertile women in China are poorly reported. The relationship between dyadic coping and the family cohesion and adaptability in infertile women was investigated. Methods: A total of 482 infertile women in the reproductive clinics of three affiliated hospitals of Lanzhou University were selected by convenience sampling method. The self-made general information questionnaire, family adaptability and cohesion evaluation scale, and dyadic coping questionnaire were used in this study. Results: The average age of infertile women was 31.734.57 years old, the duration of infertility was 28.6627.99 months, the total score of dyadic coping was 132.6625.49, the total score of family cohesion and adaptability was 101.4820.96. Significant positive correlation between dyadic coping and family cohesion and adaptability was observed (r=0.74, P<0.01). Multiple linear regression analysis showed that religious belief, number of miscarriages, relationship between family members, family intimacy and adaptability were the influencing factors of dyadic coping level in the family of infertile women (R2=0.566, P<0.01). Conclusions: The dyadic coping level of infertile women is in the medium level, which is significantly positively correlated with family intimacy and adaptability. In clinical nursing, nurses try to improve family relationship of patients to increase the level of dyadic coping of infertile women.